Bridging Pediatric and Adult Rehabilitation Services for Young Adults With Childhood-Onset Disabilities: Evaluation of the LIFEspan Model of Transitional Care - Kingsnorth, Shauna; Lindsay, Sally; Maxwell, Joanne; Hamdani, Yani; Colantonio, Angela; Zhu, Jingqin; Bayley, Mark Theodore; Macarthur, Colin (Frontiers in Pediatrics, 2021)
Background: LIFEspan (‘Living Independently and Fully Engaged’) is a linked transition service model for youth and young adults with childhood-onset disabilities offered via an inter-agency partnership between two rehabilitation hospitals (one pediatric and one adult) in Toronto, Canada. Objective: The objective was to evaluate healthcare outcomes (continuity of care and healthcare utilization) for clients enrolled in LIFEspan. Methods: A prospective, longitudinal, observational mixed-method study design was used. The intervention group comprised youth with Acquired Brain Injury (ABI) and Cerebral Palsy (CP) enrolled in LIFEspan. A prospective comparison group comprised youth with Spina Bifida (SB) who received standard care. A retrospective comparison group comprised historical, disability-matched clients (with ABI and CP) discharged prior to model introduction. Medical charts were audited to determine continuity of care, i.e., whether study participants had at least one visit to an adult provider within one year post-discharge from the pediatric hospital. Secondary outcomes related to healthcare utilization were obtained from population-based, health service administrative datasets. Data were collected over a 3-year period: two years pre and one year post pediatric discharge. Rates were estimated per person-year. Fisher’s Exact Test was used to examine differences between groups on the primary outcome, while repeated measures GEE Poisson regression was used to estimate rate ratios (post vs pre) with 95% confidence intervals for the secondary outcomes. Results: Prospective enrolment comprised 30 ABI, 48 CP, and 21 SB participants. Retrospective enrolment comprised 15 ABI and 18 CP participants. LIFEspan participants demonstrated significantly greater continuity of care (45% had engagement with adult services in the year following discharge at 18 years), compared to the prospective SB group (14%). Healthcare utilization data were inconsistent with no significant changes in frequency of physician office visits, emergency department visits, or hospitalizations for clients enrolled in LIFEspan in the year following discharge, compared to the two years prior to discharge. Conclusion: Introduction of the LIFEspan model increased continuity of care, with successful transfer from pediatric to adult services for clients enrolled. Data on longer-term follow-up are recommended for greater understanding of the degree of adult engagement and influence of LIFEspan on healthcare utilization following transfer.